THE LATEST CHANGES IN PRODUCTION STRUCTURE OF WORLD OIL PROCESSING - A. Solomonov (Вестник университета)
Development of the modern world economy is impossible without broad use of production of oil-processing industry. In modern conditions there is a serious shift in geography of world oil processing. In article the newest tendencies of change of structure of world oil-processing industry in regional aspect are estimated.